The relationship between personality traits, professional identity and job involvement of novice kindergarten teachers in Zhejiang Province, China - Yu, Wang; Yoke-Yean, Lydia Foong; Yew, Victor Goh Weng (Southeast Asia Early Childhood Journal, 2021)
In China, recent social and economic development have resulted in further attention being given to the development of preschool education. Culturally, many Chinese parents have held high expectations of their children’s early learning and academic success in later studies. Hence, a high-quality preschool service has become a contentious issue. The recent child abuse incidents involving various kindergarten teachers exposed by the media have increased parents and society’s concerns about the personal qualities and mental health of kindergarten teachers. Novice teachers are an important part of the kindergarten workforce as they are at the beginning of their careers. Their professional development level is a fundamentally important matter as it directly affects the reform and development of preschool education. The publication of a relevant preschool policy document not only emphasizes the importance of early childhood education, but also introduces new requirements for kindergarten teachers. Professional identity factors (Motivation, Self-Image, Self-efficacy, Task perception) and personality trait factors (extraversion, neuroticism, openness, conscientiousness, agreeableness) have been found in many research studies to be associated with kindergarten teachers’ job involvement. However, research on professional identity, personality traits and job involvement of novice kindergarten teachers is an undeveloped research area in China. This study will explore the relationship between personality traits, professional identity, and job involvement of novice kindergarten teachers in Zhejiang Province, China. A study of this nature will aid policy makers, the Ministry of Education, kindergarten management, and researchers on the implementation and enforcement of policies and practices that could be implemented to improve kindergarten teachers’ overall quality and teaching effectiveness in China.